2011
DOI: 10.1556/oh.2011.29226
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the JAK2V617F mutation in patients with chronic myeloproliferative neoplasia

Abstract: Incidence of the JAK2 mutation in their patients with chronic myeloproliferative neoplasia subgroups mainly corresponds to the literary data. Thrombosis ensued both in JAK positive polycythemia vera and essential thrombocythemia cases occurred nearly in the same number, but the incidence of thrombosis ensued in JAK2 negative cases did not differ significantly from the JAK2 positive patients. From these results it could be suggested that the presence or absence of JAK2 mutation in the development of thrombosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
3
1
1
Order By: Relevance
“…and CALR mutation frequencies in unexposed to IR MPN patients in this study were similar to the reported data. 9,[32][33][34][35][36][37] The frequency of MPL W515 gene mutation was lower in MPN patients in our study, in comparison to published data. 5,[38][39][40] 3.3 | Genetic variants identified in IR-exposed and IR-unexposed PMF patients WES was performed on the PBMC DNA from 30 PMF patients (13 IR-exposed and 17 unexposed PMF patients).…”
Section: Demographic and Clinical Features Of Mpn Patientscontrasting
confidence: 46%
“…and CALR mutation frequencies in unexposed to IR MPN patients in this study were similar to the reported data. 9,[32][33][34][35][36][37] The frequency of MPL W515 gene mutation was lower in MPN patients in our study, in comparison to published data. 5,[38][39][40] 3.3 | Genetic variants identified in IR-exposed and IR-unexposed PMF patients WES was performed on the PBMC DNA from 30 PMF patients (13 IR-exposed and 17 unexposed PMF patients).…”
Section: Demographic and Clinical Features Of Mpn Patientscontrasting
confidence: 46%
“…However, the present study results indirectly support the concept that the JAK2V617F mutation contributes to intrinsic changes in both megakaryocyte and platelet biology beyond the increase in cell numbers [35][36][37]. The results of another single center analyses also revealed that the JAK2 V617F (−) cases did not differ significantly from the JAK2 V617F (+) cases in the incidence of thrombosis [38][39][40]. The number of involved patients might be determinative in view of clear evaluation of the predictive value of the JAK2 V617F mutation in thrombosis [41,42].…”
Section: Discussionsupporting
confidence: 74%
“…In these patients, because signaling by the mutated kinase utilizes normal pathways, the result is an overproduction of morphologically normal blood cells, an often indolent course and usually a normal lifespan [20]. In about 30% of cases the mutation is accompanied by thromboembolic events [21], but in JAK2 negative cases thrombotic events could also be detected and the incidence of thrombosis ensuing in JAK2 negative cases does not differ significantly from JAK2 positive patients. The clinical features of these patients are not specific, and could include an increased prevalence in marrow fibrosis and splenomegaly [20], while platelet count and platelet function tests seem not to be influenced by JAK2 V617F positivity [22].…”
Section: Discussionmentioning
confidence: 99%